1994
DOI: 10.1007/bf00190741
|View full text |Cite
|
Sign up to set email alerts
|

The effect of LDL apheresis on progression of coronary artery disease in patients with familial hypercholesterolemia

Abstract: This study investigated the effect of extracorporal lipid-lowering therapy by low-density lipoprotein (LDL) apheresis on coronary artery disease in a population characterized by early development and rapid progression of atherosclerosis. We treated 32 patients aged between 15 and 63 years with drug-refractory familial hypercholesterolemia, treated once a week by immuno-specific LDL apheresis for 3 years in a controlled prospective and non-randomized trial; 25 patients (14 females and 11 males) completed the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 19 publications
0
10
0
1
Order By: Relevance
“…Previous reports have suggested that complete prevention of CHD was limited to cases administered LDL-apheresis early in the course. 23,24) However, the unchanged CSI and LVEF suggest that long-term combination therapy results in a satisfactory outcome with additional coronary angioplasty. A pathology report showed scarring of atheromatous plaque and formation of a thick fibrous cap after 7 years of LDL apheresis in a FH patient.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested that complete prevention of CHD was limited to cases administered LDL-apheresis early in the course. 23,24) However, the unchanged CSI and LVEF suggest that long-term combination therapy results in a satisfactory outcome with additional coronary angioplasty. A pathology report showed scarring of atheromatous plaque and formation of a thick fibrous cap after 7 years of LDL apheresis in a FH patient.…”
Section: Discussionmentioning
confidence: 99%
“…Therapy with statins is usually recommended [13], both high dose atorvastatin and rosuvastatin [14]. For more severe cases, LDL apheresis is often required [15], since it was shown to be able to stop the progression of coronary atherosclerosis [16].…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical trials have confirmed the benefits of LDL apheresis for prevention and slowing the progression of cardiovascular disease, 50,[56][57][58][59][60][61][62] and for other cardiovascular effects such as improvements in endothelial function, 63 coronary vasodilation, 64 microvascular flow, 65 and myocardial perfusion. 66 LDL apheresis has also been shown to promote regression of xanthomas 50 and modify a number of markers associated with vascular disease, including lipoprotein (a), an atherothrombotic marker.…”
Section: Candidates For Ldl Apheresismentioning
confidence: 99%